# Extensions 1→N→G→Q→1 with N=M4(2) and Q=C2×C6

Direct product G=N×Q with N=M4(2) and Q=C2×C6
dρLabelID
C2×C6×M4(2)96C2xC6xM4(2)192,1455

Semidirect products G=N:Q with N=M4(2) and Q=C2×C6
extensionφ:Q→Out NdρLabelID
M4(2)⋊1(C2×C6) = C3×D44D4φ: C2×C6/C3C22 ⊆ Out M4(2)244M4(2):1(C2xC6)192,886
M4(2)⋊2(C2×C6) = C3×D4.9D4φ: C2×C6/C3C22 ⊆ Out M4(2)484M4(2):2(C2xC6)192,888
M4(2)⋊3(C2×C6) = C6×C8⋊C22φ: C2×C6/C6C2 ⊆ Out M4(2)48M4(2):3(C2xC6)192,1462
M4(2)⋊4(C2×C6) = C6×C8.C22φ: C2×C6/C6C2 ⊆ Out M4(2)96M4(2):4(C2xC6)192,1463
M4(2)⋊5(C2×C6) = C3×D8⋊C22φ: C2×C6/C6C2 ⊆ Out M4(2)484M4(2):5(C2xC6)192,1464
M4(2)⋊6(C2×C6) = C3×D4○D8φ: C2×C6/C6C2 ⊆ Out M4(2)484M4(2):6(C2xC6)192,1465
M4(2)⋊7(C2×C6) = C3×D4○SD16φ: C2×C6/C6C2 ⊆ Out M4(2)484M4(2):7(C2xC6)192,1466
M4(2)⋊8(C2×C6) = C6×C4.D4φ: C2×C6/C6C2 ⊆ Out M4(2)48M4(2):8(C2xC6)192,844
M4(2)⋊9(C2×C6) = C6×C4≀C2φ: C2×C6/C6C2 ⊆ Out M4(2)48M4(2):9(C2xC6)192,853
M4(2)⋊10(C2×C6) = C3×C42⋊C22φ: C2×C6/C6C2 ⊆ Out M4(2)484M4(2):10(C2xC6)192,854
M4(2)⋊11(C2×C6) = C6×C8○D4φ: trivial image96M4(2):11(C2xC6)192,1456
M4(2)⋊12(C2×C6) = C3×Q8○M4(2)φ: trivial image484M4(2):12(C2xC6)192,1457

Non-split extensions G=N.Q with N=M4(2) and Q=C2×C6
extensionφ:Q→Out NdρLabelID
M4(2).1(C2×C6) = C3×D4.8D4φ: C2×C6/C3C22 ⊆ Out M4(2)484M4(2).1(C2xC6)192,887
M4(2).2(C2×C6) = C3×D4.10D4φ: C2×C6/C3C22 ⊆ Out M4(2)484M4(2).2(C2xC6)192,889
M4(2).3(C2×C6) = C3×D4.3D4φ: C2×C6/C3C22 ⊆ Out M4(2)484M4(2).3(C2xC6)192,904
M4(2).4(C2×C6) = C3×D4.4D4φ: C2×C6/C3C22 ⊆ Out M4(2)484M4(2).4(C2xC6)192,905
M4(2).5(C2×C6) = C3×D4.5D4φ: C2×C6/C3C22 ⊆ Out M4(2)964M4(2).5(C2xC6)192,906
M4(2).6(C2×C6) = C3×Q8○D8φ: C2×C6/C6C2 ⊆ Out M4(2)964M4(2).6(C2xC6)192,1467
M4(2).7(C2×C6) = C6×C4.10D4φ: C2×C6/C6C2 ⊆ Out M4(2)96M4(2).7(C2xC6)192,845
M4(2).8(C2×C6) = C3×M4(2).8C22φ: C2×C6/C6C2 ⊆ Out M4(2)484M4(2).8(C2xC6)192,846
M4(2).9(C2×C6) = C6×C8.C4φ: C2×C6/C6C2 ⊆ Out M4(2)96M4(2).9(C2xC6)192,862
M4(2).10(C2×C6) = C3×M4(2).C4φ: C2×C6/C6C2 ⊆ Out M4(2)484M4(2).10(C2xC6)192,863
M4(2).11(C2×C6) = C3×C8○D8φ: C2×C6/C6C2 ⊆ Out M4(2)482M4(2).11(C2xC6)192,876
M4(2).12(C2×C6) = C3×C8.26D4φ: C2×C6/C6C2 ⊆ Out M4(2)484M4(2).12(C2xC6)192,877

׿
×
𝔽